Human Factors Research in Immersive Virtual Reality Firefighter Training: A Systematic Review - Wheeler, Steven G; Engelbrecht, Hendrik; Hoermann, Simon (Frontiers in Virtual Reality, 2021)
Immersive virtual reality (VR) shows a lot of potential for the training of professionals in the emergency response domain. Firefighters occupy a unique position among emergency personnel as the threats they encounter are mainly environmental. Immersive VR therefore represents a great opportunity to be utilized for firefighter training. This systematic review summarizes the existing literature of VR firefighting training that has a specific focus on human factors and learning outcomes; as opposed to literature that solely covers the system, or simulation, with little consideration given to its user. An extensive literature search followed by rigorous filtering of publications with narrowly defined criteria was performed to aggregate results from methodologically sound user studies. The included studies provide evidence that suggests the suitability of VR firefighter training; especially in search and rescue and commander training scenarios. Although, the overall number of publications is small, the viability of VR as an ecologically valid analog to real-life training is promising. In the future, more work is needed to establish clear evidence and guidelines for how to optimize the effectiveness of VR training and to increase reliable data through appropriate research endeavours.